Regional planning in the Kilimanjara/Arusha region of Tanzania - Mosha, Aloysius Clemence (1975)
The need for regional planning in Tanzania has long been realized because in this country, as in most developing countries, there are striking contrasts and disparities between regions, clearly reflected in the very unequal opportunities to participate in the social-economic development process enjoyed by the various population groups. The sheer size of the country would make it difficult to treat the country as a single unit, even if the undeveloped transportation system did not further divide the country.